Statistical inference for generalized Pareto distribution based on progressive Type-II censored data with random removals - Azimi, Reza; Fasihi, Bahman; Azimi Sarikhanbaglu, Faramarz (International Journal of Scientific World, 2014)
In this article, We consider the estimation problems of the parameter and reliability function of the generalized Pareto distribution based on a progressively type-II censored sample with random (Binomial) removals. we use the method of maximum likelihood and Bayesian estimation to estimate parameter and reliability function. Bayesian estimates are derived under squared error and LINEX loss functions. we also construct the confidence interval for the parameter of generalized Pareto distribution based on a progressively type-II censored sample with random removals. The comparisons between different estimators are made based on simulation study. Keywords: Generalized Pareto distribution, progressive Type-II censored, random removals, Bayesian estimates, reliability function.